FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA LKM UED SP DI KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Andri Safaruddin Sibarani; Ahmad ' Rifai; Suardi ' Tarumun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to determine the financial performance of Microfinance Institutions UED SP in Rambah Samo District and determine the factors that affect the profitability of the Microfinance Institutions . Data processing is done by calculating the geometry and panel data regression analysis . There are 11 UED SP which is the object of this research . The results using geometry formulas indicate that the UED SP in Rambah Samo District has financial ratios ROA and CAR that meets the ideal standar interim financial ratios LDR NPL and ROA is still not ideal. Factors that affect the profitability of Microfinance Institutions UED SP in Rambah Samo District is LDR as variable of liquidity and NPL as variable of credit crunch. Keywords : Return On Asset, Capital Adequacy Ratio,Loan to Deposit Ratio, Non Performing Loans, BOPO